Isothermic and Kinetic Study on Removal of Methylene Blue Dye Using Anisomeles malabarica Silver Nanoparticles: An Efficient Adsorbent to Purify Dye-Contaminated Wastewater - M. Prabhahar; K. Gomathi; R. Venkatesh; V. Mago Stalany; D. S. Vijayan; Larissa R. Sassykova; S. Sendilvelan; V. Shanmuga Priya; G. O. Jijina; Rabin Selvaraj (Adsorption Science & Technology)
Remediation of industrial discharged dyes to the water bodies is much needed in the current scenario. Here in this, we prepared silver nanoparticles using Anisomeles malabarica. The synthesized nanoparticles were characterized by Fourier transform infrared study, scanning electron microscopy, dynamic scanning calorimetry, and thermogravimetric analysis. All the characterization studies suggested that the formation of silver nanoparticles was successful. The synthesized silver nanoparticles were used as an adsorbent to adsorb the methylene blue. To achieve this, optimum pH of the adsorbent to adsorb the dye was studied, and it was found to be pH 7. The adsorbent dose to adsorb the dye was found to be 0.1 g/L. From the isotherm theoretical studies, it was found that the adsorption isotherm follows Langmuir adsorption, and the qmax was found to be 97.08. From the kinetic study, the rate of the reaction follows the pseudosecond-order kinetics with regression>0.9. From the study, it was inferred the nanoparticles synthesized can act as a good adsorbent and can be used to purify the wastewater contaminated with methylene blue.